CALIFORNIA'S EVOLUTION TOWARD INTEGRATED REGIONAL WATER MANAGEMENT: A LONG-TERM VIEW - Kretsinger grabert V.; Narasimhan T.N. (My University, 2006)
Water resources sustainability hinges on interrelated physical, chemical, biological, and human processes, all of which may affect the quantity and quality of available water supplies. California's decades-long transition process from intensive and often unmanaged groundwater development toward more effective, sustainable integrated water resources management has resulted in important lessons. The process offers insights to other countries that seek to achieve sustainability. Long-term systematic groundwater and surface water monitoring programs and ongoing assessment of regional groundwater systems are an integral part of management. On local to global scales, the need for fundamental data, regional resources assessments, and increased support for scientific and technological advances is becoming increasingly apparent. The scientific community must enhance society's understanding of the essential links between basic data needs and the advancement and application of scientific approaches for effective water management. Correspondingly, scientific and political communities must coordinate common interests in endeavors toward sustainable management. Public outreach is a necessary complement to achieve sustainability goals and garner support for the programs needed to develop water policies based on sound science, manage water resources, and meet future water demands while avoiding unacceptable impacts.
Keywords: GROUNDWATER MANAGEMENT; GROUNDWATER MONITORING; SUSTAINABILITY; INTEGRATED RESOURCES MANAGEMENT; WATER POLICY